EFEKTIVITAS PEMBERIAN EKSTRAK DAUN MINT (MENTHA ARVENSIS LINN.) DAN TEKNIK RELAKSASI NAFAS DALAM TERHADAP TINGKAT NYERI MENSTRUASI PADA REMAJA PUTRI - Wijayanti Haryanto (Universitas Kusuma Husada Surakarta, 2021)
Dampak dari nyeri menstruasi (dismenorea) dapat menganggu aktivitas seorang wanita. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian ekstrak daun mint dan teknik relaksasi nafas dalam terhadap tingkat nyeri menstruasi pada remaja putri. Metode penelitian Single blind. Pengukuran tingkat nyeri menstruasi menggunakan skala numerik 0-10. Intervensi menggunakan ekstrak daun mint, teknik relaksasi nafas dalam dan kombinasi ekstrak daun mint dan teknik relaksasi nafas dalam. Penelitian dilakukan pada 30 remaja putri dibagi 2 kelompok yaitu kelompok I ekstrak daun mint dan kelompok II teknik relaksasi nafas dalam. Analisis data untuk melihat perbedaan antara sebelum dan sesudah diberikan intervensi, data berdistribusi tidak normal menggunakan uji Wilcoxon Test dengan sebelumnya dilakukan uji normalitas data dengan uji Shapiro wilk. Hasil dari penelitian yang telah dilakukan, didapatkan adanya perbedaan tingkat nyeri menstruasi sebelum dan sesudah intervensi pada kelompok I dengan nilai signifikansi lebih kecil dari nilai alpa p 0,000 (p < 0,05), ada perbedaan tingkat nyeri menstruasi sebelum dan sesudah intervensi pada kelompok II dengan nilai signifikansi lebih kecil dari nilai alpa p 0,008 (<0,05) dari hasil analisis data menggunakan uji Wilcoxon test maka dapat disimpulkan bahwa terdapat perbedaan efektivitas pemberian ekstrak daun mint dan teknik relaksasi nafas dalam terhadap tingkat nyeri menstruasi pada remaja puteri. Based on data from the WHO (World Health Organitation) the incidence of menstrual pain (dysmenorrhoea) is an average of 50% of women in every country. The incidence of menstrual pain (dysmenorrhoea) in Indonesia is 55% of productive women. The impact of menstrual pain (dysmenorrhoea) can disrupt a woman's activities. This study aims to determine the effectiveness of mint leaf extract and deep breath relaxation techniques on the level of menstrual pain in young women. Single blind research method. The measurement of the level of menstrual pain used a numerical scale of 0-10. The intervention used mint leaf extract and deep breath relaxation techniques. The study was conducted on 30 young women divided into 2 groups, namely group I mint leaf extract and group II deep breath relaxation techniques, with the inclusion criteria of girls with dysmenorrhea and not allergic to the intervention given. Data analysis to see the difference between before and after being given intervention, the data were not normally distributed using the Wilcoxon Test, with the data normality test previously being carried out with the Shapiro Wilk test. The results of the research that had been carried out showed that there were differences in the level of menstrual pain before and after being given the mint leaf extract intervention in group I with a significance value smaller than the alpha value p 0.000 (p <0.05), while in group II there were differences in pain levels. menstruation before and after the intervention of deep breath relaxation techniques in group II with a significance value smaller than the alpha p value 0.008 (<0.05) from the results of data analysis using the Wilcoxon test, it can be concluded that there is a difference in the effectiveness of giving mint leaf extract and relaxation techniques. deep breath on the level of menstrual pain in adolescent girls. Advice for young women to be able to use non-pharmacological therapy to reduce menstrual pain.